A drag force model to incorporate the reconfiguration of full-scale riparian trees under hydrodynamic loading - Patricia Xavier (Journal of Hydraulic Research, 2013)
This paper investigates the response of full-scale submerged riparian vegetation to hydrodynamic loading, using data from towing tank experiments of high resolution and accuracy. Drag force and physical property data are presented for 21 foliated and defoliated trees, including specimens of Alnus glutinosa, Populus nigra and Salix alba. The force–velocity data and contribution of foliage to the total drag are first discussed, highlighting the non-classical drag force behaviour of flexible vegetation. A theoretical model, based on the vegetative Cauchy number, is proposed from dimensional consideration to account for the bending and reconfiguration of the trees under flow action. The model links measurable vegetation properties, such as volume, height and flexural rigidity, to the force–velocity response. This allows the otherwise complex drag force of flexible vegetation to be predicted with greater accuracy than compared with a rigid cylinder approximation.